Administering Biology: How "Bathroom Bills" Criminalize and Stigmatize Trans and Gender Nonconforming People in Public Space. Issue 2 (2nd April 2020) - Murib, Zein
Abstract : Public administration scholarship pertaining to transgender individuals focuses on the implementation of nondiscrimination policies, particularly with respect to employment (Colvin 2007, 2008 ; Elias 2017 ). This literature contributes greatly to our understanding of how to maintain open and accessible workplaces for transgender people; however, the effects of the recent politicization of public restroom access for transgender people, such as North Carolina's HB 2, has yet to receive the same attention. This article argues that the recent surge of "bathroom bills" introduced across various states and localities makes opportunities for transgender and gender nonconforming people to successfully and safely inhabit public space impossible, and uses quantitative and qualitative analysis to illustrate the consequences of these policies. Focusing on seventy-one bills introduced between 2014 and 2018, this article shows that efforts to restrict bathroom access took two forms: first, legalizing discrimination against transgender and gender nonconforming people in public and second, making trans or gender nonconforming embodiment a criminal act. The article concludes with recommendations from architecture, city planning, and Trans Studies scholarship for public administration scholars and practitioners to consider as they continue to design and implement policies to address the unique needs of transgender individuals.